Analysis Of Financial Distress In The Covid 19 Pandemic Era - Vania Noventilia Mangelep; Nikolas F. Wuryaningrat; Frida M. Sumual (Jurnal Manajemen dan Ekonomi Kreatif, 2024)
This research aims to find out (1) find out whether there are differences in scores between the Altman, Springate, Zmijeski, and Grover models in predicting Financial Distress, (2) find out which companies remain healthy (green area) or do not experience Financial Distress and which companies which ones are unhealthy (red are) or experiencing Financial Distress. This research uses data from company financial reports with Special Notifications published on the Indonesia Stock Exchange website for 2020-2021. The sampling technique used purposive samples to obtain 10 companies that could be used as research. The results of this research show that the Altman model and the Grover model have the same score, namely an accuracy level of 40% and an error type of 20%, followed by the Zmijewski model with an accuracy rate of 30% and an error type of 30% and the Springate model an accuracy rate of 10% and an error type of 30%.